Plan estratégico organizacional para la empresa colchones primavera 2020 - 2024 (2020)
This research seeks to provide a general strategic plan for the company Colchones Primavera in order to project an efficient operation in the long term, which allows sustainability and competitiveness in the market and in turn make the current crisis a reason for physical and organizational reconstruction , no longer a function of external factors, if not directed from endogenous planning and from the guidelines of strategic planning.